A Tiered Female Ovarian Toxicity Screening Identifies Toxic Effects of Checkpoint Kinase 1 Inhibitors on Murine Growing Follicles - Xu, Jingshan (Toxicol Sci, 2020)
Ovarian toxicity (ovotoxicity) is one of the major side effects of pharmaceutical compounds for women at or before reproductive age. The current gold standard for screening of compounds’ ovotoxicity largely relies on preclinical investigations using whole animals. However, in vivo models are time-consuming, costly, and harmful to animals. Here, we developed a 3-tiered ovotoxicity screening approach starting from encapsulated in vitro follicle growth (eIVFG) and screened for the potential ovotoxicity of 8 preclinical compounds from AstraZeneca (AZ). Results from Tiers 1 to 2 screenings using eIVFG showed that the first 7 tested AZ compounds, AZ-A, -B, -C, -D, -E, -F, and -G, had no effect on examined mouse follicle and oocyte reproductive outcomes, including follicle survival and development, 17β-estradiol secretion, ovulation, and oocyte meiotic maturation. However, AZ-H, a preclinical compound targeting the checkpoint kinase 1 inhibitor to potentiate the anticancer effects of DNA-damaging agents, significantly promoted granulosa cell apoptosis and the entire growing follicle atresia at clinically relevant concentrations of 1 and 10 μM. The more targeted explorations in Tier 2 revealed that the ovotoxic effect of AZ-H primarily resulted from checkpoint kinase 1 inhibition in granulosa cells. Using in vivo mouse model, the Tier 3 screening confirmed the in vitro ovotoxicities of AZ-H discovered in Tiers 1 and 2. Also, although AZ-H at 0.1 μM alone was not ovotoxic, it significantly exacerbated gemcitabine-induced ovotoxicities on growing follicles. Taken together, our study demonstrates that the tiered ovotoxicity screening approach starting from eIVFG identifies and prioritizes pharmaceutical compounds of high ovotoxicity concern.